2007
DOI: 10.1007/s00248-007-9254-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Rumen Bacterial Diversity in Two Geographically Separated Sub-Species of Reindeer

Abstract: Svalbard reindeer (Rangifer tarandus platyrhynchus) live under austere nutritional conditions on the high-arctic archipelago of Svalbard, while semi-domesticated Norwegian reindeer (R. tarandus tarandus) migrate between lush coastal summer pastures and inland winter pastures with lichens on mainland Norway. Svalbard reindeer are known to have high rumen concentrations of cellulolytic bacteria, ranging from 15% of the viable population in summer to 35% in winter, compared to only 2.5% in Norwegian reindeer. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
97
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 58 publications
15
97
0
6
Order By: Relevance
“…The dominance of the Bacteroidetes and the Firmicutes phyla observed in the metagenomic results was in accordance with a number of earlier studies [Jami et al, 2014;Sundset et al, 2007] related to gut and rumen of cattle [Kalyuzhnaya et al, 2008;Kong et al, 2010] and buffalo [Singh et al, 2012]. Of these, relatively few analyzed bacterial diversity using high-throughput next-generation sequencing.…”
Section: Metagenomic Shotgun Sequencingsupporting
confidence: 73%
“…The dominance of the Bacteroidetes and the Firmicutes phyla observed in the metagenomic results was in accordance with a number of earlier studies [Jami et al, 2014;Sundset et al, 2007] related to gut and rumen of cattle [Kalyuzhnaya et al, 2008;Kong et al, 2010] and buffalo [Singh et al, 2012]. Of these, relatively few analyzed bacterial diversity using high-throughput next-generation sequencing.…”
Section: Metagenomic Shotgun Sequencingsupporting
confidence: 73%
“…In the study, we found that there were 80 cloned sequences (50%) with less than 97% of relatedness to database sequences unidentified in the goose gut previously. Sundset et al (2007) suggested that less than 97% of relatedness to database sequences may represent a new species. Moreover, the physiological role of many more bacteria than newly sequenced bacteria should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Anaerobic culture methods were those of Bryant (1972) using Hungate culture tubes (Bellco, Vineland, NJ, USA) sealed with butyl rubber septa. Bacteria were maintained on a modified M8V medium (Sundset et al 2007) in Petri dishes in an anaerobic chamber (Coy Laboratory Products, Ann Arbor, MI, USA) in an atmosphere of N 2 (90%), CO 2 (5%), and H 2 (5%). A palladium catalyst was present to remove O 2 , and the temperature in the chamber was kept at 39°C.…”
Section: Methodsmentioning
confidence: 99%
“…The bacteria were cultured under a CO 2 atmosphere in sealed boxes inside the chamber. The M8V medium contained an anaerobic M8 buffer (Olsen et al 1994) in which the rumen fluid had been replaced by a mixture of fatty acids (3.1 ml/1,000 ml medium) as described for the Deutsche Sammlung von Mikroorganismen und Zellkulturen (DSMZ, Braunschweig, Germany) medium 330 (Kopečný et al 2003) and 0.1% (wt/vol) of the following carbohydrates: xylan from Birchwood, cellobiose, glucose, starch, and maltose (Sundset et al 2007). Vitamins (1% vol/vol;Roché et al 1973) were filter sterilized through a Millex R-GS single-use filter unit (0.22 μm; Millipore, Molsheim, France) and added to the medium before use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation